Anti-inflammatory disease-modifying treatment and short-term disability progression in SPMS. (5th September 2017) - Lorscheider, Johannes; Jokubaitis, Vilija G.; Spelman, Tim; Izquierdo, Guillermo; Lugaresi, Alessandra; Havrdova, Eva; Horakova, Dana; Trojano, Maria; Duquette, Pierre; Girard, Marc; Prat, Alexandre; Grand'Maison, François; et al.
Abstract : Objective: To investigate the effect of disease-modifying treatment on short-term disability outcomes in secondary progressive multiple sclerosis (SPMS). Methods: Using MSBase, an international cohort study, we previously validated a highly accurate definition of SPMS. Here, we identified patients in MSBase who were either untreated or treated with a disease-modifying drug when meeting this definition. Propensity score matching was used to select subpopulations with comparable baseline characteristics. Disability outcomes were compared in paired, pairwise-censored analyses adjusted for treatment persistence, visit density, and relapse rates. Results: Of the 2, 381 included patients, 1, 378 patients were matchable (treated n = 689, untreated n = 689). Median pairwise-censored follow-up was 2.1 years (quartiles 1.2–3.8 years). No difference in the risk of 6-month sustained disability progression was observed between the groups (hazard ratio [HR] 0.9, 95% confidence interval [CI] 0.7–1.1, p = 0.27). We also did not find differences in any of the secondary endpoints: risk of reaching Expanded Disability Status Scale (EDSS) score ≥7 (HR 0.6, 95% CI 0.4–1.1, p = 0.10), sustained disability reduction (HR 1.0, 95% CI 0.8–1.3, p = 0.79), or change in disability burden (area under the EDSS-time curve, β = −0.05, p = 0.09). Secondary and sensitivity analyses confirmed the results. Conclusions: Our pooled analysis of the currently available disease-modifying agents used after conversion to SPMS suggests that, on average, these therapies have no substantial effect on relapse-unrelated disability outcomes measured by the EDSS up to 4 years. Classification of evidence: This study provides Class IV evidence that for patients with SPMS, disease-modifying treatment has no beneficial effect on short-term disability progression.